Pelatihan Pembuatan Ecobrick dari Sampah Plastik untuk Mendukung Gerakan Zero Waste di Rumah Belajar Kojartis Palembang - Fena Retyo Titani; Fia Dhatul Prima Kusuma; Arini Sucia (Pakis Journal Institute, 2026)
The problem of plastic waste has become a global crisis due to its difficult to decompose naturally and the practice of burning it is hazardous to health. In response to this problem, Sriwijaya State Polytechnic together with the Kojartis Palembang Learning House community held a community service activity through Ecobrick making training as a creative solution for plastic waste management. This community service is important to equip the community at the Kojartis Palembang Learning House with innovative solutions in the form of ecobrick methods to support the zero waste movement. The method used is a participatory approach that includes theoretical counseling on waste sorting, technical training on making ecobricks with a density standard of 0.33–0.7 g/ml, and the diffusion of science and technology through the transformation of ecobricks into functional furniture. The results of the activity showed a significant increase in participant awareness, where participants who were initially unfamiliar with ecobricks are now able to process household plastic waste into useful products such as educational tables. These results conclude that ecobrick training is not just training, but also creates innovative learning media that increases students' collective awareness of environmental sustainability.